Proof of Pythagoras theorem
Answers
Answered by
2
proof
take a triangle abc
take one big sqaure....in it take a small square
AREA OF WHOLE SQUARE
it is a big square....with each side having a length of a+b,so the total area is:
A=(a+b)(a+b)
AREA OF THE PIECES
now let's add up the areas of all the smaller pieces:
first,the smaller(tilted) sqaure has an area of:c^2
each of the four triangles has an area of:ab/2
so all four of them together is:4ab/2=2ab
adding up the tilted square and the 4 triangles gives:A=c^2+2ab
BOTH AREAS MUST BE EQUAL
(a+b)(a+b)=c^2+2ab
(a+b)(a+b)=c^2+2ab
a^2+2ab+b^2=c^2+2ab
subtract"2ab" from both sides
a^2+b^2=c^2
HENCE PROVED
take a triangle abc
take one big sqaure....in it take a small square
AREA OF WHOLE SQUARE
it is a big square....with each side having a length of a+b,so the total area is:
A=(a+b)(a+b)
AREA OF THE PIECES
now let's add up the areas of all the smaller pieces:
first,the smaller(tilted) sqaure has an area of:c^2
each of the four triangles has an area of:ab/2
so all four of them together is:4ab/2=2ab
adding up the tilted square and the 4 triangles gives:A=c^2+2ab
BOTH AREAS MUST BE EQUAL
(a+b)(a+b)=c^2+2ab
(a+b)(a+b)=c^2+2ab
a^2+2ab+b^2=c^2+2ab
subtract"2ab" from both sides
a^2+b^2=c^2
HENCE PROVED
SINGHisKING11:
thanks a lot Didi
Answered by
4
HELLO !!!....
_____________________
Given : A right ΔABC right angled at B
To prove : AC2 = AB2 + BC2
Construction : Draw AD ⊥ AC
Proof : ΔABD and ΔABC
∠ADB = ∠ABC = 90°
∠BAD = ∠BAC (common)
∴ ΔADB ∼ ΔABC (by AA similarly criterion)
=> AD/AB = AB /AC
⇒ AD × AC = AB2 ...... (1)
Now In ΔBDC and ΔABC
∠BDC = ∠ABC = 90°
∠BCD = ∠BCA (common)
∴ ΔBDC ∼ ΔABC (by AA similarly criterion)
=> CD/BC = BC/AC
⇒ CD × AC = BC2 ........ (2)
Adding (1) and (2) we get
AB2 + BC2 = AD × AC + CD × AC
= AC (AD + CD)
= AC × AC = AC2
∴ AC2 = AB2 + BC2
________________________
HOPE IT HELPS U DEAR :))
CHEERS !!!!
# NIKKY ✌✌
_____________________
Given : A right ΔABC right angled at B
To prove : AC2 = AB2 + BC2
Construction : Draw AD ⊥ AC
Proof : ΔABD and ΔABC
∠ADB = ∠ABC = 90°
∠BAD = ∠BAC (common)
∴ ΔADB ∼ ΔABC (by AA similarly criterion)
=> AD/AB = AB /AC
⇒ AD × AC = AB2 ...... (1)
Now In ΔBDC and ΔABC
∠BDC = ∠ABC = 90°
∠BCD = ∠BCA (common)
∴ ΔBDC ∼ ΔABC (by AA similarly criterion)
=> CD/BC = BC/AC
⇒ CD × AC = BC2 ........ (2)
Adding (1) and (2) we get
AB2 + BC2 = AD × AC + CD × AC
= AC (AD + CD)
= AC × AC = AC2
∴ AC2 = AB2 + BC2
________________________
HOPE IT HELPS U DEAR :))
CHEERS !!!!
# NIKKY ✌✌
Attachments:
![](https://hi-static.z-dn.net/files/db5/e70bb4d5fef93567bd0c8bc0492ceac1.jpg)
Similar questions
French,
8 months ago
Computer Science,
8 months ago
Math,
8 months ago
Economy,
1 year ago
CBSE BOARD XII,
1 year ago
Math,
1 year ago